TELDOM: mednarodno omrežje za diagnostiko pigmentnih sprememb kože - Bartenjev, Igor (Radiology and oncology (Ljubljana), 1999)
TELDOM will provide a network infrastructure for delivering innovative, high quality, user friendlly and easy accessible medical services to citizens for diagnosis of pigmented skin lesions and tumors at the point of care regardlessof location by using advanced information technologies. Digital images will be send to th ecentres of excellence for diagnoses and returning to th e points of care. Contact between general physicians and specialists will be strenghtened and the transfer of medical knowledge from centers to remote areas intensified.
Keywords: Computer communication networks; dermatologija; Diagnosis; diagnostika; družinska medicina; Family practice; kožne spremembe; Nevus, pigmented; pigmentni nevusi; računalniška mreža